Antimicrobial Activity of a Novel Flavonol Glycoside Isolated from the Roots of Clitoria ternatea Linn. - YADAVA, R.N.; VERMA, VIKASH (Asian Journal of Chemistry, 2010)
A novel biologically active flavonol glycoside 1, m.p. 260-261 °C, m.f. C33H40O20, [M+] 756 (ElMS) was isolated from the ethyl acetate soluble fraction of the defatted seeds of Clitoria ternatea Linn. It was characterized as a novel biologically active flavonol glycoside 3,5,4'-trihydroxy-7- methoxyflavonol-3-O-α-L-xylopyranosyl-( 1→3 )-O-β-D-galactopyranosyl (1→6)-O-β-D-glucopyranoside by several colour reactions, spectral analysis and chemical degradations. The compound 1 showed antimicrobial activity against various becteria and fungi.